Debt-for-development exchanges history and new applications (Cambridge Cambridge University Press, 2011)
Debt-for-development exchanges are an important financing tool for development. They make debt relief more politically and practically attractive to donor countries, and serve the development of recipient countries through the cancellation of external debt and the funding of important development projects. This book commences by chronicling the emergence of debt-for-development exchanges from their forebears, debt-equity exchanges, and analyzes why debt for development suffers from very few of the problems that plagued debt equity. The book analyzes the different types of debt-for-development exchanges and the different ways they have been used by all donor nations that have made use of them. The book then explores a range of critical perspectives on exchanges and concludes by considering a wide range of new and innovative uses for the funds generated by exchanges.
Includes bibliographical references and index.
Keywords: Economic development projects -Finance -Law and legislation